ANALISIS EFEKTIVITAS DAN EFISIENSI LAPORAN KEUANGAN PEMERINTAH KECAMATAN UNGARAN KABUPATEN SEMARANG TAHUN 2017-2018 - DWI PUJIASTUTI; KARIMATUS SA'DIYAH; SYLVIA INDAH LESTARI; NUR KABIB; MUAMMAR TAUFIQI LUTFI MUSTOFA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
The purpose of this study was to determine the effectiveness and efficiency financial statements of the district government of Ungaran, Semarang district in 2017-2018. The type of data used is secondary data in the form of a budget realization report. The approach taken is quantitative descriptive, calculated using the ratio of efficiency and effectiveness ratio. The results of the research in the district of Ungaran Semarang regency showed that is the level of effectiveness research Ungaran District Semarang Regency in 2017-2018 seen from the effectiveness ratio experienced different effectiveness levels in 2017 experienced by 107.16% which is in the category of very effective. Whereas in 2018 only 79.06% was included in the less effective category. Where in 2017 the efficiency level of 92.27% was caused by the amount of budget that was realized 90% -100% and in 2018 it was at the level of 94.68%.